Emotions and feelings: historical and multidisciplinary coordinates of a key field of study for Education Sciences - Mahamud Angulo, Kira (Avances en Supervisión Educativa, 2012)
Emotions and feelings: historical and multidisciplinary coordinates in a field of study crucial for education sciences. Kira Mahamud, UNED (Spanish National Distance Learning University) The author establishes as objectives three converging ideas: calling into question the “novelty” of the topic by recalling and highlighting the range and relevance of the contributions of important personalities in previous centuries; emphasizing the historical conception of “continuity” and “process” in the building up of knowledge around emotions and feelings; and, staking a claim for the need of an interdisciplinary approach to research by taking into account the progress made in biology, neurology, psychology, linguistics and sociology.